Educational Uses of the Digital World for Human Development (LEARNing Landscapes, 2013)
This article discusses several enduring features of the digital world in relation to the dramatically changing global context and visibility of the human condition. Based on the author’s experience as an educator and researcher, she explains that interactivity, multi-modality, and information storage are ripe for advancing students’ creative and critical interactions with diverse others and themselves. With the digital world as a focal point, although by no means the only communication medium, educators are in unique positions to guide contemporary human development, which is increasingly an interdependent individual-societal process, thereby requiring knowledge of realities beyond one’s own.
Keywords: digital world; interactivity; multi-modality; information storage; creative; critical; interaction